Impact of CPAP treatment on leptin and adiponectin in adults with coronary artery disease and nonsleepy obstructive sleep apnoea in the RICCADSA trial - BALCAN, MEHMET BARAN; AY, NADİYE PINAR (ELSEVIER, 2020)
Background: Increased leptin and decreased adiponectin levels are reported in coronary artery disease (CAD) as well as in obstructive sleep apnoea (OSA). Less is known regarding the impact of continuous positive airway pressure (CPAP) on these biomarkers. We aimed to determine variables associated with leptin and adiponectin in adults with CAD and nonsleepy OSA, and evaluate the effect of CPAP adjusted for confounding factors. Methods: This was one of the secondary outcomes of the RICCADSA trial, conducted in Sweden between 2005 and 2013. From 244 revascularized CAD and OSA patients (apnoeaehypopnoea index > 15/h) without excessive daytime sleepiness (Epworth Sleepiness Scale score <10), 196 with blood samples at baseline, after 3, and 12 months were included in the randomized controlled trial arm; of those, 98 were allocated to auto-titrating CPAP, and 98 to no-CPAP. Results: No significant changes in leptin and adiponectin levels were observed during follow-up, whereas Body-Mass-Index and waist circumference increased in both CPAP and no-CPAP groups with no significant between-group differences. Alterations in plasma leptin were determined by changes in waist circumference (beta coefficient 2.47; 95% confidence interval 0.77-4.40), whereas none of the analyzed parameters was predictive for changes in adiponectin levels. No association was found with CPAP adherence. Conclusions: CPAP had no significant effect on leptin and adiponectin in this cohort of nonsleepy OSA patients. An increase in waist circumference predicted an increase in plasma levels of leptin after 12 months, suggesting that lifestyle modifications should be given priority in adults with CAD and OSA regardless of CPAP treatment. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Positive airway pressure; Weight gain; Leptin; Adiponectin; Sleep apnoea; POSITIVE AIRWAY PRESSURE; C-REACTIVE PROTEIN; INSULIN-RESISTANCE; PLASMA LEPTIN; RISK-FACTORS; ASSOCIATION; RATIONALE; GHRELIN; OBESITY; EVENTS